Threatened habitat at Great Salt Lake: Importance of shallow-water and brackish habitats to Wilson's and Red-necked phalaropes. (23rd April 2019) - Frank, Maureen G; Conover, Michael R
Abstract: Great Salt Lake (GSL) is the largest hypersaline lake in North America and is the fall staging area for a high proportion of North America's Wilson's Phalaropes ( Phalaropus tricolor ) and Red-necked Phalaropes ( Phalaropus lobatus ). Unfortunately, diversion of freshwater for agriculture and development has decreased the size of GSL by 48%. To assess the potential impact of a smaller GSL on phalaropes, we collected data from 2013 to 2015 from sites where large, dense flocks of phalaropes congregated and sites where there were no phalaropes. At each site, we measured the densities of invertebrates that were preyed upon by phalaropes, including larval and adult brine flies (Ephydridae), adult brine shrimp ( Artemia franciscana ), chironomid larvae (Chironomidae), and corixid adults (Corixidae). Abiotic characteristics measured included water depth, water salinity, water temperature, wind speed, and benthic substrate. We analyzed high-salinity sites separately from low-salinity sites because they contained different invertebrates. High-salinity sites were in Carrington and Gilbert bays and were relatively deep (mostly <2 m). At the high-salinity sites, phalaropes exhibited a preference for sites with an abundance of adult brine flies and for microbialite substrates. The low-salinity sites were in Ogden and Farmington bays and were shallow (<1 m). At low-salinity sites, large phalarope flocks were more likely to occur at sites that were shallower, less saline, and had a high biomass of benthic macroinvertebrates. Our results indicate that physical features and prey availability are both important in determining phalarope habitat use at GSL. Phalaropes prefer to use shallower parts of GSL and brackish waters. These areas will be especially impacted by decreased freshwater inflow into GSL.